ANALISIS STRATEGI PEMASARAN KARET DI KECAMATAN KAMPAR KABUPATEN KAMPAR - Dayu Ananda; Shorea Khaswarina; Yeni Kusumawaty (Indonesian Journal of Agricultural Economics, 2021)
Rubber is one of the leading and strategic plantation commodities, its role is quite large in encouraging the people's economy. Effective rubber marketing is the hope of farmers, so that farmers get a good rubber marketing strategy. The aim of the study was to develop recommendations for rubber marketing strategies in Kampa District, Kampar Regency. This study used survey methods, observations, and interviews with the sampling technique using snowball sampling, and the number of respondents was 27 people. SWOT analysis is used to develop a rubber marketing strategy and the discussion is presented in a qualitative descriptive manner. The results of the analysis of rubber marketing strategies in Kampa District, Kampar Regency are 1). Rubber marketing to factories is carried out through the Joint Business Group and the requirements for joining the Joint Business Group must not be burdensome to members as stipulated in the AD/ART of KUB; 2). The Joint Business Group cooperates with BUMDes to strengthen capital and build rubber storage warehouses; 3). The Joint Business Group evaluates the rubber factory's assessment of the rubber sold and the farmers improve the quality of the rubber according to the established standards; 4). The government helps rubber farmers make an MoU on rubber marketing with rubber factories.